2009
DOI: 10.1021/jp807644e
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Mechanism of 2,3-Dihydro-1,5-benzodiazepin-2-ones Hydrazinolysis

Abstract: Density functional theory approach was used for the 4-methyl-2,3-dihydro-1,5-benzodiazepin-2-one compound to determine the mechanism of hydrazinolysis of 4-substituted 2,3-dihydro-1,5-benzodiazepin-2-ones. Single point computations at the MP2/6-311+G(d,p)//B3LYP/6-31G(d) level were performed for the more precise energy prediction. The solvent effect was taken into account by carrying out single point calculations using the PCM methodology. The obtained results show that in the investigating mechanism the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Full gas-phase geometry optimizations were performed using the density functional theory with the Beck's three-parameter nonlocal exchange functional and the gradient-corrected functional of Lee et al (B3LYP), [72][73][74] due to its successful application in a number of hydrazinolysis [75,76] and analogous substituted hydrazine systems, [9,11,12] obtaining reasonable molecular structures, vibrational frequencies, and bond energies. Basis set of double-f split valence plus polarization and diffusion quality (6-31þG(d,p)) [77] was employed in all optimization calculations.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Full gas-phase geometry optimizations were performed using the density functional theory with the Beck's three-parameter nonlocal exchange functional and the gradient-corrected functional of Lee et al (B3LYP), [72][73][74] due to its successful application in a number of hydrazinolysis [75,76] and analogous substituted hydrazine systems, [9,11,12] obtaining reasonable molecular structures, vibrational frequencies, and bond energies. Basis set of double-f split valence plus polarization and diffusion quality (6-31þG(d,p)) [77] was employed in all optimization calculations.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Okovytyy and co-workers described the hyrazinolysis mechanism of 2,3-dihidro-1,5benzodiazipine-2-thiones 13 and the 2,3-dihidro-1,5-benzodiazipin-2-ones. 14 They have examined in detail the possible mechanisms of the initial step of the reactions and concluded that the benzodiazipine systems were attacked by a hydrazine molecule toward the azomethine bond. The system considered here is similar to 3-R- [1,2,4]triazino [2,3-c]quinazolin-2-ones (condensed aromatic and heterocyclic rings with azomethine bond), and we suggest that interaction with the nucleophile will proceed in a similar manner.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Despite the abundance of data based on experimental results, only a few studies have dealt with the overall mechanism of nucleophile addition reactions. Okovytyy and co-workers described the hyrazinolysis mechanism of 2,3-dihidro-1,5-benzodiazipine-2-thiones and the 2,3-dihidro-1,5-benzodiazipin-2-ones .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recyclization of heterocyclic compounds in reactions with hydrazine and its derivatives has been extensively studied experimentally and has been shown to be very important in organic synthesis. Despite numerous predictions of the possible mechanisms of the recyclization processes, theoretical verification for the proposed mechanisms by quantum mechanical calculations has not been yet accomplished. In a recent paper, we reported the theoretical investigation on hydrazinolysis of 4-methyl-2,3-dihydro-1,5-benzodiazepin-2-one leading to 3-methylpyrazolone-5. To broaden our analysis of the 1,5-benzodiazepines, in this study, we investigated the mechanism of the recyclization reaction which takes place during interaction of 2,3-dihydro-1,5-benzodiazepine-2-thiones with hydrazine (Scheme ).…”
Section: Introductionmentioning
confidence: 99%